Factors Affecting the Quality of Life for the Elderly in the Northeast - Yangkham, Piyawan; Masaunjik, Nava; Chalermchit, Auscharaporn; Ruksasri, Pornwadee; Wanichkittikul, Kotchanipa (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Thailand has placed importance on supporting an aging society by making it a strategic plan for the country. By starting to prepare the National Elderly Plan. The purposes of this research were: 1) to study the quality of life of the elderly in the Northeast, and 2) to compare personal characteristics and quality of life of the elderly in the Northeast. Methodology: Collecting data from 400 elderly in the Northeast and a set of questionnaires were the research tool. Statistics used for data analysis were mean, standard deviation, t-test, and one-way ANOVA. Results: 1) The elderly had opinions about the quality of life in general aspect at a high level and had an average of 3.98, the averages are arranged in descending order as follows: the mental aspect had an average of 4.07, social integration aspect had an average of 4.05, rights and liberties aspect had an average of 3.95, self-development aspect had an average of 3.89, and physical aspect had an average of 3.87 2) Elderly people with gender, age, and education level Monthly income is different. The quality of life of the elderly in the Northeast is no different. Conclusion: The elderly had opinions about quality of life in general aspect at a high level and elderly people with gender, age, and education level Monthly income is different. The quality of life of the elderly in the Northeast is no different.